Relationship-building in the post-acceleration phase of corporate accelerators: empirical evidence from Germany - Alexander Kramer; Dominik K. Kanbach (International Entrepreneurship and Management Journal, 2023)
Corporate accelerators have become a relevant intermediary that connects startups and corporations. Their strategic goal is to establish close relationships between startups and corporations that add value for both parties in the long term. While in principle startups go through an acceleration phase successfully, they may struggle to build meaningful relationships with the accelerator's corporate parent thereafter. In research, the post-acceleration phase and its challenges for corporations and startups has not been adequately addressed to date. Therefore, the goal of this article is to shed light on how corporations and startups collaborate after startups leave an accelerator programme, and which factors hinder successful relationship-building. Grounding on 21 corporate accelerator cases containing data from 99 semi-structured interviews with corporate accelerator managers and startup alumni of accelerator programmes, we present different forms of post-programme collaboration and outline obstacles of post-programme relationship-building. Our results emphasise a key role of business units in successful relationship-building and indicate legitimacy problems of accelerators within its corporate organisation. We also provide guidance for corporations, accelerators, and startups on how to increase the success of post-programme collaboration by demonstrating manifold challenges of post-programme collaboration and showing ways how to overcome them.
Keywords: 650; Corporate accelerator; Strategic collaboration; Relationship-building; Corporate venturing; Startup assistance programmes